The Media Coverage of the 2016 Presidential Elections: A Content Analysis of the Daily Guide, the Enquirer and the Ghanaian Times - Bagbara, Tanko (UniMAC-GIJ, 2017)
The main objective of this study is to have a content analysis of the Ghanaian media relative to the coverage of the 2016 presidential campaigns for NDC and NPP using Daily Guide, the Enquirer and the Ghanaian Times. Specific objectives would include assessing the performance of the print media houses on their coverage of the NPP and NDC campaign, determining the factors that shaped their coverage systems and assessing the challenges that the print media houses encountered in the coverage of the 2016 presidential campaigns for the NDC and NPP. The descriptive survey research design was used for the study. The population of the study were the management and staff of the three print media houses namely The Ghanaian Times, Daily Guide and The Enquirer. For the purpose of this study, both primary and secondary data were used. Data analysis was done using content analysis of the newspaper sampled. The findings of the study revealed that contrary to previous Ghanaian study, which played down the issue of partiality in Ghanaian journalism practice, horse race framing of election campaigns is increasingly gaining grounds in the practice of political journalism in Ghana. This trend seems to be contributing to a two-party democratic governance in the country as is the situation in the United States, for instance. To illustrates this point here, all the characteristics of horse race framing such as who is winning the race, public opinion polls, focusing on crowd attendance at campaign rallies all go to project the two main political parties in Ghana, the NDC and the NPP to the disadvantage of the snlaller political parties. Recommendations were that to enhance and enrich the public sphere, it is recommended that a more interpretative news style of reporting policy issues.
Thesis